Scalable Push Pull architecture for retrieving student information request and response with data wrappers (International Journal of Engineering and Computer Science, 2015)
The concept of web services deals with request and response services for storing and retrieving data. As the data focus on dynamism, the strategy becomes highly impeccable to deal with the growing data volumes. The data service also retrieves the unwanted data that come along with the request. The strategy should satisfy the demand and balance the volume and provide exact result using the pull push architecture. The proposed work address the same that produce feasible result for student information gathering based on the information request by them and the response made in return. The work also address the data wrapper set that encapsulate specific information target based on the request.